Complications related to invasive hemodynamic monitors during adult liver transplantation. (2nd September 2013) - Lu, Shu Y.; Matsusaki, Takashi; Abuelkasem, Ezeldeen; Sturdevant, Mark L.; Humar, Abhinav; Hilmi, Ibtesam A.; Planinsic, Raymond M.; Sakai, Tetsuro
Abstract The rate of complications directly related to invasive monitors during liver transplantation (LT) was reviewed in 1206 consecutive adult LTs performed over 8.6 yr (1/1/2004–7/31/2012). The designated anesthesiologists placed intra‐operative monitors, including two arterial catheters (via the radial and the right femoral arteries), central venous catheters (a 9 Fr. catheter and an 18 Fr. veno‐venous bypass [VVB] return cannula in an internal jugular vein), a pulmonary artery catheter, and a transesophageal echocardiography (TEE) probe. A 17 Fr. VVB drainage cannula was placed via the left femoral vein. No Clavien–Dindo Grade V (death) or Grade IV (organ dysfunction) complication was identified. Nine Grade III complications (requiring surgical intervention) and 15 Grade II complications (conservative treatment) were noted. Seven (0.58% in 1206 cases) were related to a femoral arterial line with Grade III of four; seven (0.58%) were due to VVB return cannula in the femoral vein with Grade III of one; four (0.33%) were related to central venous catheters with Grade III of two; four (0.33%) were due to a TEE probe with Grade III of two; and two minor complications (0.17%) that were related to a radial arterial line. No complication was observed with a pulmonary arterial catheter. Current invasive monitors placed during LT have an acceptable risk.